ANTIBACTERIAL ACTIVITY OF THREE STORED OLIVE OILS AND MENTHA - H, Boukhebti*; A. N., Chaker, . Mekhadm N. E. (university of eloued جامعة الوادي, 2020)
This study aimed to evaluate the antibacterial activity of three samples of stored olive oils (01 year, 12 years and 33 years) and essential oil of Mentha aquatica L. Two Gram positive bacteria strains: Citrobacter freundii ATCC 8090, Staphylococcus aureus ATCC 25923 and five Gram negative bacteria strains: Pseudomonas aeruginosa ATCC 27853, Escherichia coli ATCC 25922, klebsiella pneumoniae ATCC 700603, Bacillus subtilis ATCC 6633 and Schigella sonnei were used in the present study. The results show that the olive oil stored for 33 years has evident antibacterial activity against bacteria strains used, especially against Citrobacter freundii ATCC 8090, Bacillus subtilis ATCC 6633 and Staphylococcus aureus ATCC 25923, whereas all samples have no effect on klebsiella pneumoniae ATCC 700603 and Pseudomonas aeruginosa ATCC 27853.
artical
Keywords: Olea europea L., Mentha aquatica L., stored olive oil, essential oil, antibacterial activity.